2007
DOI: 10.1590/s0101-20612007000500011
|View full text |Cite
|
Sign up to set email alerts
|

Testes sensoriais de aceitação da beterraba vermelha (Beta vulgaris ssp. vulgaris L.), cv. Early Wonder, minimamente processada e irradiada

Abstract: A beterraba vermelha (variedade hortícola, cultivar Early Wonder) foi cultivada na área experimental do Departamento de Fitotecnia do Instituto de Agronomia da Universidade Federal Rural do Rio de Janeiro. Após a colheita, as raízes foram minimamente processadas, embaladas e submetidas a diferentes doses de radiação gama (0; 0,5; 1,0; e 1,5 kGy), sendo em seguida armazenadas, por 20 dias, a 8 °C. Durante o período de armazenamento, aos: 1, 9, 13 e 20 dias, foram realizados testes sensoriais, nos quais 12 avali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Red beet is regarded as a good potential source of antioxidants and phenols , and it also expresses anticancer and radio-protective properties , . It has also been shown to contain other health promoting constituents and is therefore regarded as a good enrichment of the human diet . Furthermore, to date no studies have been published that investigate differences due to the production method in the contents of sugars, organic acids, total phenolic content, and the antioxidative activity in red beet.…”
Section: Introductionmentioning
confidence: 99%
“…Red beet is regarded as a good potential source of antioxidants and phenols , and it also expresses anticancer and radio-protective properties , . It has also been shown to contain other health promoting constituents and is therefore regarded as a good enrichment of the human diet . Furthermore, to date no studies have been published that investigate differences due to the production method in the contents of sugars, organic acids, total phenolic content, and the antioxidative activity in red beet.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Zhang et al (2006) reported that the quality of freshly cut lettuce irradiated at 1 kGy was maintained for 8 days of storage. Furthermore, Hernandes et al (2007) showed that irradiation maintains the sensory characteristics of red beets relative to the untreated control sample.…”
Section: Effect Of E-beam Irradiation On the Sensory Quality Of Raspberriesmentioning
confidence: 98%
“…Beta vulgaris (beterraba vermelha) também possui uma grande quantidade de nutrientes como a proteína, lipídios, carboidratos, fibra alimentar, cinzas, e minerais como o cálcio e magnésio (TACO, 2011). Sua coloração é decorrente da presença das betacianinas (pigmentos vermelhos que pertence ao grupo das betalaínas) (Hernandes, 2007). A produção de farinha é uma maneira de aproveitar esses resíduos que ainda pode ter utilidade, contribuindo para a redução de perdas dentro da cadeia produtiva, além de estimular a agricultura familiar (PARAIZO, 2019).…”
Section: Introductionunclassified